Impact of Intellectual Disability on the Family Economy in Calabar, Cross River State, Nigeria - Adeleke, Owoade Philip; Ewa, James Abua; Olayi, James Eburikuri; Orim, Samuel Orim (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
This study investigated the impact of intellectual disability (ID) on the family economy in Calabar, Cross River State, Nigeria. The cost of parenting a child with ID in Nigeria is overwhelming as there is no state provision for the care of this group, consequently imposing burden on the parents. Parents of persons with ID in Calabar South Local Government Area, Cross River State, Nigeria, constituted the study population. The study sample includes 150 parents of persons with ID. Intellectual Disability and Family Economy Assessment Scale (r = 0.877) was used for data collection. Data were analysed using frequency count and percentage. The study revealed that ID significantly affects the family economy and education of siblings and persons with ID in Calabar, Cross River State, Nigeria. The impact of ID on the family economy in the study area is generally negative. Nigerian government should put in place the necessary social facility that will help reduce the impact of the disability on the families.